PENYULUHAN TENTANG MAKANAN SEHAT DAN INOVATIF UNTUK ANAK USIA DINI - Handayani, Noviasari; Gunarmi, Gunarmi; Isnawati Hadi, Selasih Putri (Jurnal Pengabdian Masyarakat, 2024)
Early Childhood according to Law no. 20 of 2003 are children aged 0-6 years. The growth of early childhood is very dependent on the child's health which is influenced by the healthy food consumed. The health problem of early childhood caused by malnutrition which results in disrupted growth is stunting. This service aims to change the mother's lifestyle/habits after the child reaches an early age by providing food that is unbalanced and less attractive. This community service will be carried out in Sumurejo Village, Gunungpati District, Semarang City. The target was 18 families in Dawis Amarilis, Sumurejo Subdistrict. There are four competency points that are expected to be obtained by pregnant women and breastfeeding mothers after this counseling, namely: Knowledge (knowledge) Mothers will have knowledge and understanding regarding the benefits of healthy food innovation for early childhood. Mother's skills are able to process food to be more innovative and highly nutritious. Attitude (Behavior) To form a conscious attitude about the importance of preparing innovative and nutritious food. Product (product) Obtain a leaflet about innovative and nutritious food.